Synthesis, applications and Structure-Activity Relationship (SAR) of cinnamic acid derivatives: a review (Research, Society and Development, 2021)
The article aims to analyze the progress of the evolution of cinnamic acid derivatives through a bibliographic review, describing the main synthetic routes in obtaining this class, as well as remarkable biological applications and application of the structure-activity relationship (SAR) as a strategy for design pharmacologically active molecules. The methodology used consists of reading and analyzing articles, whose approach is descriptive, with data being collected regarding the therapeutic potential of derivatives of cinnamic acid and its relationship with structural scaffolding, as well as the most widely used synthetic approaches. As a result, it was observed that cinnamic acid and its derivatives from natural sources can be synthesized in appreciable quantities with varied synthetic routes, as well as being candidates for therapeutic agents, since they have several therapeutic applications against diabetes, infectious and degenerative diseases, among others, in addition to presenting activity such as pest control, which has attracted the attention of academic and industrial researchers. These compounds are highly versatile since their activity is intrinsically associated with the mode of interaction between the structure and its molecular target. However, in nature they are obtained in small quantities, therefore, the development of new approaches of synthetic methodologies to obtain such compounds in substantial quantities and linked to medicinal chemistry can contribute to the development of very effective bioactive molecules in comparison with their precursors.